You can also set this up as an algebraic equation.

First decide what variables you want to use, I am going to chose X and Y.

So, my two numbers are X and Y

I also know from the question that their sum is 36, so ....

X + Y = 36

I also know that their product is 320, so ...

X.Y = 320

Now you have simultaneous equations. To deal with these you want to take one equation, and isolate one variable.

Using X + Y = 36

I will isolate X, so ....

X = 36 - Y

Now I want to substitute this into my second equation of X.Y = 320

(36 - Y).Y = 320

Expand ....

36Y - Y^2 = 320

Y^2 - 36Y -320 = 0

Y = (-b +- square root of b^2 - 4ac)/2a

When you solve using this method, there are two values of Y .... And by substitution the two values of X

16 and 20

First decide what variables you want to use, I am going to chose X and Y.

So, my two numbers are X and Y

I also know from the question that their sum is 36, so ....

X + Y = 36

I also know that their product is 320, so ...

X.Y = 320

Now you have simultaneous equations. To deal with these you want to take one equation, and isolate one variable.

Using X + Y = 36

I will isolate X, so ....

X = 36 - Y

Now I want to substitute this into my second equation of X.Y = 320

(36 - Y).Y = 320

Expand ....

36Y - Y^2 = 320

Y^2 - 36Y -320 = 0

Y = (-b +- square root of b^2 - 4ac)/2a

When you solve using this method, there are two values of Y .... And by substitution the two values of X

16 and 20